2012
DOI: 10.4149/bll_2012_150
|View full text |Cite
|
Sign up to set email alerts
|

The effects of three training methods endurance, resistance and concurrent on adiponectin resting levels in overweighed untrained men

Abstract: The purpose of present study was to investigate the impacts of endurance, resistance and concurrent training on adiponectin resting levels of sedentary men. Forty-four sedentary students were randomly assigned to one of four groups: endurance training (ET; 22 ± 0.89 yr, n=12), resistance training (RT, 21 ± 1.57 yr, n=9), concurrent training (CT, 21.38 ± 2.6 yr, n=14) and control group (CG, n=10). After primary measurements, blood samples were drawn with subjects in fasting and resting state for determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Screening of the titles and abstracts excluded a further 33,344 articles and, therefore, 290 full texts were retrieved. Finally, 24 papers were included in the study [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], of which the two following papers related to the same study conducted on the same population and the same intervention but reported on the different outcomes: Nunes et al [ 47 ] and Martins et al [ 48 ]. Moreover, one manuscript was published in two journals [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Screening of the titles and abstracts excluded a further 33,344 articles and, therefore, 290 full texts were retrieved. Finally, 24 papers were included in the study [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], of which the two following papers related to the same study conducted on the same population and the same intervention but reported on the different outcomes: Nunes et al [ 47 ] and Martins et al [ 48 ]. Moreover, one manuscript was published in two journals [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies were designed as randomised trials and published between 2005 [ 45 ] and 2021 [ 23 ]. Most studies were performed in Asia (eight in Iran [ 17 , 18 , 20 , 37 , 38 , 41 , 42 , 44 , 46 ] two in Japan [ 19 , 45 ], and one in South Korea [ 24 ]); six studies were conducted in Europe (two in Poland [ 14 , 23 ], one each in Denmark [ 21 ], Finland [ 40 ], Greece [ 15 ], and Norway [ 43 ]); three in South America (Brazil [ 25 , 47 , 48 ]); and three studies were performed in Australia and Oceania (two in Australia [ 16 , 39 ] and one in New Zealand [ 22 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations